When Your Doctor “Gets It” and “Gets You”: The Critical Role of Competence and Warmth in the Patient–Provider Interaction - Howe, Lauren C.; Leibowitz, Kari A.; Crum, Alia J. (Frontiers in Psychiatry, 2019)
Background: Research demonstrates that the placebo effect can influence the effectiveness of medical treatments and accounts for a significant proportion of healing in many conditions. However, providers may differ in the degree to which they consciously or unconsciously leverage the forces that produce placebo effects in clinical practice. Some studies suggest that the manner in which providers interact with patients shapes the magnitude of placebo effects, but this research has yet to distill the specific dimensions of patient-provider interactions that are most likely to influence placebo response and the mechanisms through which aspects of patient-provider interactions impact placebo response. Methods: We offer a simplifying and unifying framework in which interactions that boost placebo response can be dissected into two key dimensions: patients’ perceptions of competence, or whether a doctor “gets it” (i.e., displays of efficiency, knowledge, and skill), and patients’ perceptions of warmth, or whether a doctor “gets me” (i.e., displays of personal engagement, connection, and care for the patient). Results: First, we discuss how this framework builds on past research in psychology on social perception of competence and warmth and in medical literature on models of effective medical care, patient satisfaction, and patient-provider interactions. Then we consider possible mechanisms through which competence and warmth may affect the placebo response in healthcare. Finally, we share original data from patients and providers highlighting how this framework applies to healthcare. Both patient and provider data illustrate actionable ways providers can demonstrate competence and warmth to patients. Discussion: We conclude with recommendations for how researchers and practitioners alike can more systematically consider the role of provider competence and warmth in patient-provider interactions to deepen our understanding of placebo effects and, ultimately, enable providers to boost placebo effects alongside active medications (i.e., with known medical ingredients) and treatment in clinical care.